Emerging issues perspectives and challenges of India's foreign economic policy: focus on finance and trade in the 21 century - Raipuria, Kalyan (New Delhi, 1998)
The paper focusses on India's commercial and economic interaction as the most vital component of its foreign economic policy and relations. Among other things, it considers the challenge to bring intrinsic strength to the country's position in the world economy; discusses the trend in favour of market-based foreign economic relations; and suggests that in future, foreign market fundamentals will have to be strengthened. And also that the new challenge of the emerging economic prowess of China will have to be met. Going by the 'SWOT analysis of India's foreign economic policy, it finds that there are more strengths than weaknesses and greater opportunities than threats. To maximise strengths, it is imperative that opportunities are fully utilised. After a close re view of weaknesses and threats, it suggests a substantial and coordinated policy effort, that includes an innovative and proactive approach, a firm grasp of emerging market-based economic relations and behaviour of nation states in order to derive lessons for the future, and above all, to increase domestic economic strength and maximise the nation's wealth.
Keywords: International economics